HUBUNGAN ANTARA PENGGUNAAN TEKNOLOGI MEDIA BK DENGAN KEPUASAN LAYANAN BIMBINGAN KLASIKAL - Nur Aeni Sanjaya (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2018)
Abstract : This study aims to determine the relationship between the use of media technology guidance and counseling and the satisfaction of classical guidance services of class VIII MTs Negeri 6 Sleman using a quantitative approach. The independent variable in this research is the use of media technology guidance and counseling (X), while the dependent variable is the satisfaction of classical guidance services (Y). This study is a research with 63 student respondents. The main data collection techniques are scale, while interviews and documentation are supplementary data. Data analysis using Product Moment correlation study from Pearson to obtained the results of hypothesis testing, with the help of SPSS 16.0 for Windows. The results of this research indicate that there is a positive and highly significant relationship between the use of media technology guidance and counseling with the satisfaction of classical guidance services of class VIII MTs Negeri 6 Sleman which has a correlation coefficient of 0.406 with sig. (2-tailed) = 0.001 with N = 63 at 1% significance level. From these data it can be concluded that there is a positive relationship and very significant, then the hypothesis is accepted and proved true. Therefore, the higher the use of media technology guidance and counseling, the higher the satisfaction of classical guidance services. On the contrary, if it gets lower the use of media technology guidance and counseling, the lower the satisfaction of classical guidance services.